The IL‐36 receptor pathway regulates Aspergillus fumigatus‐induced Th1 and Th17 responses. Issue 2 (18th December 2012) - Gresnigt, Mark S.; Rösler, Berenice; Jacobs, Cor W.M.; Becker, Katharina. L.; Joosten, Leo A.B.; van der Meer, Jos W.M.; Netea, Mihai G.; Dinarello, Charles A.; van de Veerdonk, Frank L.
<x xml:space="preserve">Abstract</x> IL‐1 drives Th responses, particularly Th17, in host defense. Sharing the same co‐receptor, the IL‐1 family member IL‐36 exhibits properties similar to those of IL‐1. In the present study, we investigated the role of IL‐36 in Aspergillus fumigatus‐induced human Th responses. We observed that different morphological forms of A. fumigatus variably increase steady‐state mRNA of IL‐36 subfamily members. IL‐36α is not significantly induced by any morphological form of Aspergillus. Most strikingly, IL‐36γ is significantly induced by live A. fumigatus conidia and heat‐killed hyphae, whereas IL‐36Ra (IL‐36 receptor antagonist) is significantly induced by heat‐killed conidia, hyphae, and live conidia. We also observed that IL‐36γ expression is dependent on the dectin‐1/Syk and TLR4 signaling pathway. In contrast, TLR2 and CR3 inhibit IL‐36γ expression. The biological relevance of IL‐36 induction by Aspergillus is demonstrated by experiments showing that inhibition of the IL‐36 receptor by IL‐36Ra reduces Aspergillus‐induced IL‐17 and IFN‐γ. These data describe that IL‐36‐dependent signals are a novel cytokine pathway that regulates Th responses induced by A. fumigatus, and demonstrate a role for TLR4 and dectin‐1 in the induction of IL‐36γ.